Nordic Ties and British Lives? Migrant Capital and the Case of Nordic Migrants Living in London - Koikkalainen, Saara (2019)
As a hub of finance, art, design and science, the city of London has long attracted migrants interested in study and career opportunities or simply excited about living in an open, global city. Over the last few decades, it has also been a key migration destination for Europeans originating from the Nordic countries. Based on survey data gathered through an online questionnaire, this article focuses on Nordic migrants currently living in London. Since the June 2016 referendum, the Brexit process has forced these voluntary and rather privileged migrants to question their inclusion in British society. This article discusses the role of migrant capital, i.e., the skills and resources created as a result of migration, at a time of uncertainty brought on by Brexit. It examines how these migrants see their position within the social hierarchy of the city and its job market, as well as within the local and transnational networks they maintain to their countries of origin. Their Nordic background is valuable thanks to the cultural capital embodied in their habitus as well as the social capital available via the Nordic networks in UK and transnationally.